Uji Toksisitas Bacillus thuringiensis terhadap Ulat Kubis (Plutella xylostella) pada Tanaman Sawi (Brassica juncea L.) - Inggrit Kartika Celiandra; Akhmad Rizali; Muhammad Imam Nugraha (Universitas Lambung Mangkurat, 2022)
One of the obstacles in the cultivation of mustard plants is the attack of pests. The pest that usually attacks mustard plants is the cabbage caterpillar (P. xylostella). The attack of the cabbage caterpillar (P. xylostella) caused serious damage to the mustard plant which resulted in decreased quality and quantity of mustard production. One of the alternatives in controlling cabbage caterpillar (P. xylostella) is to use the biological agent B. thuringiensis. B. thuringiensis is an organic pest control microbe that is cheap, easy to use and environmentally friendly. The purpose of this study was to determine the toxicity of several bioinsecticide products with active ingredients of B. thuringiensis to cabbage caterpillars (P. xylostella). This study used a completely randomized design method (CRD) with a single factor treatment in the form of several bioinsecticide products with active ingredients of B. thuringiensis which consisted of three treatments, namely A1: Turex WP, A2: Cutlass WP and A3: B-Tox. The results showed that testing of several bioinsecticide products with the active ingredient of B. thuringiensis affected cabbage caterpillars (P. xylostella). The highest killing rate of cabbage caterpillar (P. xylostella) reached 0.91 worms/hour (A2) and the highest mortality percentage against cabbage caterpillar (P. xylostella) reached 90% (A2).